1999
DOI: 10.1302/0301-620x.81b4.9282
|View full text |Cite
|
Sign up to set email alerts
|

The influence of crystallinity of the hydroxyapatite coating on the fixation of implants

Abstract: We inserted two hydroxyapatite (HA)-coated implants with crystallinities of either 50% (HA-50%) or 75% (HA-75%) bilaterally into the medial femoral condyles of the knees of 16 dogs. The implants were allocated to two groups with implantation periods of 16 and 32 weeks. They were weight-bearing and subjected to controlled micromovement of 250 microm during each gait cycle. After 16 weeks, mechanical fixation of the HA-50% implants was increased threefold as compared with the HA-75% implants. After 32 weeks ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…Extensive in vitro and in vivo research suggested that CaP coatings are essential for early bone performance when compared with Ti implants (Overgaard et al, 1997(Overgaard et al, , 1999Ong et al, 1998Ong et al, , 2002Ferraz et al, 1999;Blokhuis et al, 2000;Moroni et al, 2002;ter Brugge and Jansen, 2002). Previous characterizations indicated that as-sputtered coatings were amorphous (Ong et al, 1992) but displayed an HA-type crystalline structure after heat treatments (Ong and Lucas, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive in vitro and in vivo research suggested that CaP coatings are essential for early bone performance when compared with Ti implants (Overgaard et al, 1997(Overgaard et al, , 1999Ong et al, 1998Ong et al, , 2002Ferraz et al, 1999;Blokhuis et al, 2000;Moroni et al, 2002;ter Brugge and Jansen, 2002). Previous characterizations indicated that as-sputtered coatings were amorphous (Ong et al, 1992) but displayed an HA-type crystalline structure after heat treatments (Ong and Lucas, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…After 32 weeks, both crystallinity have the same bonding strength with bones -the bonding of 75% crystallinity HA increased and 50% remains the same. However, the low crystallinity induced higher degree of cell growth, Figure 31 shows the bone growth on 50% and 75% crystallinity HA [76]. The arrow shows the HA layer at the interface indicating that higher bone growth was on 50% crystallinity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been reported that both the resistant dissolving capacity of an amorphous HA coating and its stability in a body-fluid environment are lower than those of a crystalline one. [24][25][26][27][28][29] If such an amorphous HA coating were implanted into the human body directly, then it would be invalidated in a short period and fail to satisfy clinical requirements. Therefore, a post-annealing treatment was performed on the gradient coating with water vapor to convert the amorphous coating to a crystalline one.…”
Section: Morphology Observation and Composition Analysismentioning
confidence: 99%